TREATMENT OF PATIENTS WITH PURULENT-NECROTIC COMPLICATIONS SYNDROME OF DIABETIC FOOT - Matmurotov K. J.; Ismailov U. S.; Atajanov T. Sh.; Yakhubov I. Y.; Yorkulov A. Sh.; Kosimov N. A. (Modern American Journals, 2025)
The authors proposed a new method of treatment of patients with purulent-necrotic complications of diabetic foot using a hydrosurgery system VERSAJET ™. A comparative analysis of treatment outcomes of two groups of patients with complicated forms of diabetic foot was conducted. For the treatment of patients of the main group was used hydrosurgery method. At patients of the control group surgical approach was determined by conventional methods. Application hydrosurgery system led to a reduction in terms of wound healing, reduce postoperative complications from 37.5% to 7.1%.
Keywords: Diabetic foot syndrome, necrectomy, gidrohirurgicheskaya system VERSAJET™